Syllables and Stress of the Lithuanian Language - Garšva, Kazimieras (Respectus Philologicus, 2004)
The stressed syllable of the Lithuanian language is separated from the unstressed syllables by the main tone, loudness and duration. There are 11 prosodemes of the stress in the common Lithuanian language and five prosodemes of the stress in the dialect of North Panevėžiškiai, in which the stress is retracted. The stressed syllable of the Lithuanian word phonetically and phonologically is separated from other syllables by the main tone, loudness and duration of the pronunciation. If the accents of stressed diphthongs (acute and circumflex) are considered as a stress, in some cases the emphasis of different components of diphthongs in the same syllable had to be considered as a stress, too. The stress is a supersegmental feature of a word performing the culminant and distinctive function. The stress occurs phonologically in disyllables and polysyllables, and phonetically in monosyllables.